Digital Marketing Strategies in Medical Tourism : Evaluating Praga Medica’s Effectiveness in Attracting International Patients - Smejkalová, Nela; Lhotáková, Markéta, 1971-; Kachlová, Jana; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
With the growing number of individuals seeking more affordable, accessible, and high-quality medical care abroad, effective marketing strategies and an understanding of the factors influencing patient decision-making, trust-building, and overall satisfaction are becoming increasingly important. The internet plays a crucial role in reaching international clients, therefore, medical tourism agencies should use digital channels to differentiate themselves and attract a broader global audience. This bachelor’s thesis defines the field of medical tourism, explores the Czech market, and highlights the role of medical facilitators in the patient journey. It focuses specifically on key digital marketing channels and practices used for medical tourism marketing. Praga Medica, a leading medical tourism facilitator in the Czech Republic, serves as the central case study. Through content analysis, competitor benchmarking, and semi-structured interviews with patients, the thesis evaluates Praga Medica’s digital marketing strategies, their effectiveness in attracting international clients, and their impact on trust, decision-making, and satisfaction. Based on the findings, specific recommendations are proposed to improve the company’s online presence and competitiveness. The study identifies opportunities to enhance the website’s usability, navigation, and SEO performance. It also recommends increasing social media awareness and engagement, developing more actionable online advertising, and encouraging more patient reviews. Consistent communication and support throughout the patient journey can further enhance trust and credibility.
Vedoucí práce: Markéta Lhotáková
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses